Erratum / Corrigendum / Retraction - MKTS, Editorial (MEDIA KOMUNIKASI TEKNIK SIPIL, 2019)
RETRACTION TO:Priyonggo, K., 2004. Investigate Buckling Loads of Columns of Regular Polygon Cross-Section with Constant Volume and Clamped Ends. MEDIA KOMUNIKASI TEKNIK SIPIL, [Online] Volume 12(2), pp. 23-30. https://doi.org/10.14710/mkts.v12i2.2678Priyonggo, K., 2005.  Improvement of Road Network Reliability under Different Route Choice Principles. MEDIA KOMUNIKASI TEKNIK SIPIL, [Online] Volume 13(1), pp. 16-19.https://doi.org/10.14710/mkts.v13i1.3892 Leksono, B. T., 2006. A Parametric Study of an Offshore Concrete Pile under Combined Loading Conditions using Finite Element Method. MEDIA KOMUNIKASI TEKNIK SIPIL, [Online] Volume 14(2), pp. 156-168. https://doi.org/10.14710/mkts.v14i2.3943These articles have been retracted by Publisher based on publication misconduct by the author.